SUGGESTION ACTS PERFORMED BY ENGLISH INSTRUCTORS OF CONVERSATION CLASS IN LANGUAGE CENTRE OF ANDALAS UNIVERSITY - Maldin, Siska Amelia (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
This study aimed to analyze analyzes suggestion acts that were spoken by English instructors in conversation classes at the Andalas University Language Center. The purposes purposes of this study are are to identify and explain explain the types of speech acts, taxonomies, modifications, and reasons of the instructor expressing the speech. This study is descriptive study which data are taken from two conversation class instructors in language centre of Andalas University This study is descriptive study which data are taken from two conversation class instructors in language centre of Andalas University. The data are in the form of transcriptions, research notes, and interviews. The data are in the form of transcription, research notes, and interviews. The data are in the form of The data are in the form of transcription, research notes,, and interviews. The instruments used are observation sheets, audio recordings,, and interview guidelines. The findings indicate indicate that the two instructors expressed different suggestions at each meeting. The highest intensity of appearance of suggestion acts is is seen in the first meeting of the first instructor and the third meeting of the second instructor. Furthermore, the two instructors also express express the same type of taxonomy/suggestion acts as conventionalized forms. Then, a similar fact is is found from the modified aspect, namely subjectivizer. The reasons reason why the instructor expresses suggestions are are influenced by social distance, power,, and imposition. Based on these findings, it is is implied that the suggestion actions action taken by the instructors instructors are are influenced by the culture of the community and the class context.